Effectiveness of quality improvement interventions for patient safety in radiology: a systematic review protocol. (September 2016) - Jabin, Shafiqur Rahman; Schultz, Tim; Hibbert, Peter; Mandel, Catherine; Runciman, William
Abstract : Review question/objective: The objective of this review is to find the best available evidence regarding effectiveness of quality improvement interventions in clinical radiology and the experiences and perspectives of staff and patients. More specifically, the review questions are: How effective are the interventions that may improve or affect patient safety and quality in clinical radiology? What are the experiences and perspectives of staff and patients of patient safety and quality improvement interventions?